Моделирование температурного состояния реактора термохимической деструкции изношенных автомобильных шин - Сталинский, Дмитрий Витальевич; Скоромный, А. Л.; Синозацкий, А. М. (НТУ "ХПИ", 2011)
The statement of heat conductivity problem in the fragment of reactor thermo chemical destruction for waste tires utilization and solve by the finite element method are considered in the article. The dependence of change maximal differences of temperature on the reactor’s work surface by the step between tubular electric heating element, which placed by perimeter of reactor’s chamber is found and specified its magnitude S = 0,042 m.
Keywords: термохимическая деструкция; автомобильные шины; энергоресурсы; разложение резины; утилизация; подвод теплоты; теплоноситель; теплообмен